2005
DOI: 10.2135/cropsci2005.0562
|View full text |Cite
|
Sign up to set email alerts
|

Tall Fescue Photomorphogenesis as Influenced by Changes in the Spectral Composition and Light Intensity

Abstract: The influence of deciduous foliage shade on turfgrass development has not been fully investigated. Previous research neglects changes in spectral distribution, e.g., red:far‐red light (R:FR) ratios common of foliage shade. Turfgrass plants may respond simultaneously but in different ways to changes in light intensity and spectral composition. A field study was conducted in 2001–2002 at the Ohio Turfgrass Research and Educational Facility, Columbus, OH. Two tall fescue (Festuca arundinacea Schreb.) cultivars of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 32 publications
6
62
1
Order By: Relevance
“…The site effect was quite large for mass plant -1 , SLW, and tillers plant -1 . Shade-affected growth responses were reported previously for tall fescue in pot (Allard et al 1991a) and field studies (Burner and MacKown 2006;Kephart and Buxton 1993;Wherley et al 2005). The LER was about one-tenth that reported for pot-grown tall fescue (Allard et al 1991a) regardless of treatment.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The site effect was quite large for mass plant -1 , SLW, and tillers plant -1 . Shade-affected growth responses were reported previously for tall fescue in pot (Allard et al 1991a) and field studies (Burner and MacKown 2006;Kephart and Buxton 1993;Wherley et al 2005). The LER was about one-tenth that reported for pot-grown tall fescue (Allard et al 1991a) regardless of treatment.…”
Section: Discussionsupporting
confidence: 65%
“…The PAR received in pine alleys suggested that while shading was intense, it was not at the light compensation point (Beard 1973). In addition to a reduction in PAR, the red: far red light ratio in the pine alley might have been about one-half that in the meadow, which could reduce tillering, root mass, and chlorophyll concentration of tall fescue (Wherley et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been reported in many turfgrass species e.g. St. Augustinegrass (Wherley et al, 2013), tall fescue (Wherley et al, 2005) and, seashore paspalum (Jiang et al, 2004). The peak chlorophyll content at 75% shade level for all species in this study suggested the employment of similar mechanism in adapting to the low light conditions.…”
Section: Leaf Chlorophyllsupporting
confidence: 84%
“…Smith (1982) indicated that the blue-absorbing photoreceptor present in plants acts to measure light quantity and that the pigment phytochrome can act to detect the red : far-red ratio as an indicator of light quality. Blue light may have important implications for stomatal control, causing stomatal opening (Morison and Jarvis, 1983), while the red : far-red ratio is known to influence photomorphogenesis, heating regulation, as well as stem elongation and chlorophyll synthesis (Gates, 1965;Smith, 1982;Wherley et al, 2005;Casal, 2013). Ritchie (1997) reported the ability of Pseudotsuga menziesii seedlings to detect the presence of nearby trees via changes in light quality and the ability to adjust their growth by altering their allometry.…”
Section: Introductionmentioning
confidence: 99%